Untrained birds' ability to recognise predators with changed body size and colouration in a field experiment - Antonová, Kateřina; Veselý, Petr; Fuchs, Roman (BMC ecology and evolution, 2021)
BACKGROUND: During recognition process, multiple parameters of the encountered stimulus may play a role. Previous studies with wild birds identified the importance of several salient features (e.g., eyes, beak, prominent elements of colouration) which birds use to recognise other bird species, such as predators or nest parasites. In the present study, we observed the responses of passerines visiting winter feeders to stimuli in the form of dummies of Eurasian sparrowhawk which were modified in body size and/or colouration but always carried the salient features of raptors (hooked beak, talons) and one species-specific feature of the sparrowhawk (yellow eyes). In the vicinity of a feeder, we placed a dummy of an unmodified sparrowhawk, life-sized sparrowhawk with pigeon, great tit, or robin colouration, a small, great tit-sized sparrowhawk dummy with unmodified or pigeon colouration, or an unmodified pigeon dummy, which functioned as a harmless control. Then we measured how it affected the number of visits. RESULTS: We found that birds were less afraid of small dummies regardless of their colouration than they were of life-sized raptor dummies or even the pigeon dummy. This contrasts with the results of a previous laboratory experiment where great tits' reaction to small dummies was comparably fearful to their response to life-size dummies. In our experiment, birds were also not afraid of life-sized dummies with modified colouration except for a robin-coloured dummy, which caused an equally significant fear reaction as an unmodified sparrowhawk dummy. It is likely that this dummy resembled the colouration of a male sparrowhawk closely enough to cause this effect. CONCLUSIONS: Based on our observations, we conclude that birds use contextual features to evaluate the size of other birds. Distance and familiar reference points seem to play an important part in this process.
Keywords: rozpoznávání (psychologie); Animals, Wild; Body Size; zpěvní ptáci; Passeriformes; Animals; divoká zvířata; Songbirds; Body size; Colouration; mužské pohlaví; Male; Birds; velikost těla; Recognition, Psychology; zvířata; Predator recognition